Simultaneous Dual Echo Gadolinium Enhanced MR-PET for Evaluation of PET Tracer Delivery in Altered Pathophysiology - Cowin, Gary J; Mardon, Karine; Houston, Zachary H.; Bhalla, Rajiv; Stimson, Damion H. R.; Thurecht, Kristofer J.; Brereton, Ian M. (Frontiers in Physics, 2022)
Efficacy of diagnostics and therapeutics for brain tumours can be modulated by vascular delivery and blood brain barrier permeability. Simultaneous dynamic gadolinium MR-PET enables independent assessment of vascular delivery and blood brain barrier integrity in a brain tumour animal model in the presence of a PET tracer. Dual echo dynamic gadolinium enhanced gradient echo imaging allows simultaneous calculation of T2* and T1 images from the TE image pairs. Relaxivity values then enabled determination of independent T2*- and T1-derived gadolinium concentrations simultaneously with measurement of [18F]DPA-714 neuroinflammation radiotracer delivery. Separate T2*- and T1-derived gadolinium concentrations curves were derived in a selection of tumours and normal tissue, reflecting vascular delivery and tissue uptake. Changes in the PET activity curves were seen in tumours and normal tissue, reflecting changes in the MR derived dynamic curves. The dramatic changes in the MR-derived vascular delivery and tissue uptake estimates may improve the understanding of the alteration of delivery and uptake of new theranostic agents.